Suppression of ϒ(1S) at forward rapidity in Pb-Pb collisions at sNN=2.76 TeV - Abelev, B.; Adam, J.; Adamovã, D.; Aggarwal, M.M.; Agnello, M.; Agostinelli, A.; Agrawal, N.; Ahammed, Z.; Ahmad, N.; Ahmed, I.; Ahn, S.U.; Ahn, S.A.; et al. (Elsevier, 2014)
We report on the measurement of the inclusive Υ (1S) production in Pb–Pb collisions at √sNN = 2.76 TeV carried out at forward rapidity (2.5 < y < 4) and down to zero transverse momentum using its μ+μ− decay channel with the ALICE detector at the Large Hadron Collider. A strong suppression of the inclusive Υ (1S) yield is observed with respect to pp collisions scaled by the number of independent nucleon–nucleon collisions. The nuclear modification factor, for events in the 0–90% centrality range, amounts to 0.30 ± 0.05(stat) ± 0.04(syst). The observed Υ (1S) suppression tends to increase with the centrality of the collision and seems more pronounced than in corresponding mid-rapidity measurements. Our results are compared with model calculations, which are found to underestimate the measured suppression and fail to reproduce its rapidity dependence.
Keywords: Υ(1S) production; Pb–Pb collisions; https://purl.org/pe-repo/ocde/ford#1.03.04